The role of alternatives in the cognitive processing of German demonstratives: insights from online and offline processing - Çokal, Derya; von Heusinger, Klaus (Frontiers in Language Sciences, 2024)
This study, employing eye-tracking reading and sentence completion experiments, explores the impact of competing antecedents on the German demonstratives der and dieser. It challenges prior assumptions, revealing that in competitive alternative antecedent contexts, processing dieser initially posed challenges, indicating sensitivity to alternatives. Dieser exhibited less processing difficulties than der, potentially influenced by a register effect. Consistent with previous findings, in the offline task, references to the non-prominent entity were similar for both demonstratives, but our online experiment shows functional differences in cognitive processes between the two in reading. Our results suggest that Thematic Role accounts better explain antecedent preferences for der and dieser than Centering Theory.